The Implementation of Restorative Care and Factors Associated with Resident Outcomes in Long-Term Care Facilities in Taiwan - Wang, Yu-Hua (Int J Environ Res Public Health, 2019)
This study aimed to analyze how restorative care is implemented in long-term care facilities and factors associated with resident outcomes in Taiwan. A one-group pre-test and post-test design was adopted in 24 long-term care facilities by collecting a sample of 310 participants at the baseline and 210 at six months. Participants were residents aged 65 or over, and were being constrained, used diapers, or were bedridden, or a combination of these. Their physical and mental functions were measured using Activities of Daily Living (ADLs), Instrumental Activities of Daily Living (IADLs), Mini-Mental State Examination (MMSE), Geriatric Depression Scale-15 (GDS-15), and EuroQol-5D (EQ-5D). Mean differences in the outcomes were analyzed, and mixed effect models were used to examine influencing factors. The results showed that most of the participants had good family support. However, participants with better family support were more likely to drop out. Improvements were found in the residents’ outcomes on physical function, depression and quality of life. Social support was a significant influencing factor on most of the outcomes. In conclusion, restorative care was found to have positive effects on residents’ physical function and helped maintain mental function. Sufficient support and communication between participants, families, and staff in facilities are key factors leading to positive outcomes.